Chasing Vermeer - Balliett, Blue; Helquist, Brett (New York : Scholastic Press, 2005)
When strange and seemingly unrelated events start to happen and a precious Vermeer painting disappears, eleven-year-olds Petra and Calder combine their talents to solve an international art scandal.
English language and literature.
Keywords: Vermeer, Johannes, -- 1632-1675 -- Fiction; Art -- Fiction; Mystery and detective stories